Pengaruh Ekonomi Bitcoin terhadap Jumlah Uang Beredar di Indonesia dengan Volatilitas Bitcoin sebagai Variabel Intervening - Riyan Yusuf Octafia; Amalia Nur Chasanah; Usman Usman; Bara Zaretta (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of the Bitcoin economy on the money supply (M1) in Indonesia, with Bitcoin volatility as an intervening variable. Using a quantitative approach, the data consists of 36 monthly time-series observations from 2022 to 2024. Data analysis techniques include regression analysis adjusted with the Prais-Winsten method to address autocorrelation issues, the Sobel test for mediation analysis, and path analysis. The results indicate that the Bitcoin economy has a direct, positive, and significant effect on the money supply (M1) in Indonesia. However, the Bitcoin economy was found to have a negative and non-significant effect on Bitcoin volatility. Similarly, Bitcoin volatility exerts a negative but non-significant influence on the money supply (M1). The Sobel test results prove that Bitcoin volatility does not function as an intervening variable mediating the relationship between the Bitcoin economy and the money supply (M1). These findings suggest that while the expansion of the Bitcoin ecosystem encourages an increase in domestic monetary liquidity, the price fluctuations of digital assets have not yet become a transmission channel that significantly disrupts the stability of national monetary aggregates.